Obesity Parameters in Polycystic Ovary Syndrome in Duhok City - Rasool, Suzan Omer (Sulaimani Journal for Pure and Applied Sciences, 2021)
Background: PCOS is linked to obesity, increased risk of metabolic syndrome, and cardiovascular adverse manifestations. About 30-75% of women with PCOS are obese. Aim of the study: This study aimed to estimate the obesity parameters in PCOS and compare these results to women without PCOS. Methods: In this cross-sectional study, the BMI and Waist/Hip ratio of 150 women with established PCOS according to the diagnostic criteria were compared to 100 age-matched healthy women. Results: 95 patients and 50 of the comparison group were obese. The difference in the mean of BMI in PCOS patients and the comparison group was statistically highly significant (P < 0.001). The Waist/Hip ratio was above 0.85 in 91 patients and 73 healthy individuals and statistically, the difference was not significant when a cut-off point of 0.85 is considered (P > 0.05 unpaired T-test). Conclusions: BMI was found to be a more sensitive parameter than Waist/Hip ratio, in the determination of obesity-associated with PCO.
Keywords: Obesity; PCOS; BMI; W/H